Effects of sugar molecules on the rheological and tribological properties and on the microstructure of agarose-based fluid gels - Ghebremedhin, Marta; Seiffert, Sebastian; Vilgis, Thomas A. (Frontiers in Soft Matter, 2024)
Introduction: Fluid gels exhibit a unique flow behaviour. Their pronounced viscoelastic behaviour arises from irregular microgel particles, leading to plasticity and yielding, as well as a characteristic transition from a solid to a fluid-like state. This is defined by both the core and the surface structures of the particles. Adding co-solutes such as sucrose alters the network properties at the molecular scale, affecting texture and lubrication. This study investigates how the microscopic changes due to sucrose addition correlate with macroscopic changes. Material and methods: Agarose fluid gels with varying sucrose concentrations were prepared and studied using the rheometer. Temperature dependent viscosity behaviour during gelation under shear was investigated in situ. Light microscopy and particle size measurements were examined, and complemented by amplitude, frequency and flow sweeps as well as tribological studies. These tests allow us to understand the influence of sucrose on the particle network formation. Results and discussion: Sucrose concentration influenced the sizes, shapes, and interconnected network structure of the microgel particles. These microstructural changes are closely related to the dynamic competition between gelation and disruption of the agarose chains during shear, which directly influences the rheological and tribological properties of the resulting fluid gels. Additionally, the association of the agarose chains and their gelation process is also influenced depending on whether the sucrose or agarose was first dissolved in water. The experimental observations suggest specific molecular mechanisms, explaining the role of sucrose in structure formation of agarose-based fluid gels. These results have the potential to expand the applications of fluid gels, which play a crucial role in modifying the texture and flow behaviour of foods and beverages, particularly in addressing challenges such as dysphagia.